2018
DOI: 10.1186/s12862-018-1183-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Plutella species show deep divergence despite the capacity to hybridize

Abstract: BackgroundUnderstanding genomic and phenotypic diversity among cryptic pest taxa has important implications for the management of pests and diseases. The diamondback moth, Plutella xylostella L., has been intensively studied due to its ability to evolve insecticide resistance and status as the world’s most destructive pest of brassicaceous crops. The surprise discovery of a cryptic species endemic to Australia, Plutella australiana Landry & Hebert, raised questions regarding the distribution, ecological traits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 88 publications
0
40
1
Order By: Relevance
“…A better understanding of migration or transport routes enabling P. xylostella to colonize the world would help explain why this is the case. Several studies have found Australian P. xylostella mtDNA genomes have very low levels of diversity (Juric, et al 2016;Perry, et al 2018;Saw, et al 2006), which is indicative of a population bottleneck (and other factors), while we found…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…A better understanding of migration or transport routes enabling P. xylostella to colonize the world would help explain why this is the case. Several studies have found Australian P. xylostella mtDNA genomes have very low levels of diversity (Juric, et al 2016;Perry, et al 2018;Saw, et al 2006), which is indicative of a population bottleneck (and other factors), while we found…”
Section: Discussioncontrasting
confidence: 52%
“…The fortuitous identification of Plutella australiana was unexpected and raised initial concern over its pest status and whether specific management practices were required. P. australiana populations collected from across southern Australia (Perry, et al 2018) and Australian P. xylostella (Endersby, et al 2006) lack genetic structure, showing these species are highly mobile. Adaptive introgression of advantageous traits from one of these species into the other could potentially spread across the Australian continent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations